Maqasid al-Shariah as a Complementary Framework for Conventional Bioethics: Application in Malaysian Assisted Reproductive Technology (ART) Fatwa - Ibrahim, Abdul Halim; Rahman, Noor Naemah Abdul; Saifuddeen, Shaikh Mohd (Springer Verlag, 2018)
Rapid development in the area of assisted reproductive technology (ART), has benefited mankind by addressing reproductive problems. However, the emergence of new technologies and techniques raises various issues and discussions among physicians and the masses, especially on issues related to bioethics. Apart from solutions provided using conventional bioethics framework, solutions can also be derived via a complementary framework of bioethics based on the Higher Objectives of the Divine Law (Maqasid al-Shariah) in tackling these problems. This approach in the Islamic World has been applied and localised in the Malaysian context. Thus, this paper highlights a conceptual theoretical framework for solving current bioethical issues, with a special focus on ART in the Malaysian context, and compares this theory with conventional theories of bioethics.